PERAN SERAT PANGAN DALAM REGULASI RASA KENYANG DAN PENGENDALIAN BERAT BADAN: LITERATURE REVIEW - Rizka Aulia Br Saragih; Putri Fachira; Mutiara Pratiwi; Laila Agustina; Chantika Imelia Br. Sinaga; Dimas Rizqi; Ida Duma Riris (STKIP Subang, 2026)
Obesity is a health problem characterized by excessive accumulation of body fat due to an imbalance between energy intake and expenditure. One of the factors involved in weight control is dietary fiber intake. Fiber is known to increase satiety, regulate appetite, and help control energy intake. This study aims to examine the role of dietary fiber in regulating satiety and weight control through a literature review method. Data were obtained from various scientific articles and relevant research findings, and then analyzed descriptively. The results of the study indicate that dietary fiber operates through various mechanisms, including increasing stomach volume, slowing gastric emptying, forming a gel in the digestive tract, and influencing the release of hormones that regulate hunger and satiety. Various studies also indicate that adequate fiber intake is associated with a reduced risk of overweight and obesity, and contributes to improved metabolic health. Additionally, the development of high-fiber foods based on local ingredients has the potential to serve as an alternative for increasing the public’s fiber intake. Nevertheless, obesity is a multifactorial condition that is also influenced by behavioral and psychological factors, such as emotional eating. Therefore, efforts to control obesity should focus on increasing fiber intake, adopting a balanced diet, managing emotions, and adopting a healthy lifestyle in general.